ESTUDO LONGITUDINAL DE INDIVÍDUOS COM DOENÇA DE CHAGAS DE REGIÃO ENDÊMICA BRASILEIRA: A COORTE SAMITROP - Souza, Andréia Brito de; Lacerda, Amanda Mota; Ferreira, Ariela Mota; Damasceno, Renata Fiúza; Sabino, Éster Cerdeira; Ribeiro, Antônio Luiz Pinho; Vieira, Thallyta Maria; Haikal , Desirée Sant’Ana; Silva, Amanda Karoline Pinheiro (Revista Unimontes Científica, 2021)
the SaMi-Trop cohort (Center for Research in Tropical Medicine of São PauloMinas Gerais), a multicentric study of patients with Chagas’ disease (CD) designed by scientists from four Brazilian public universities, has been conducted since 2013 in regions endemic to the state of Minas Gerais (MG). Objective: to present and describe how the SaMiTrop cohort and its main results are being conducted, also promoting a local return aimed at municipal managers. Methods: participants were recruited through the database of the Minas Gerais Telecare Network (RTMG). To date, two collections have been made, the baseline that took place in the years 2013 and 2014 and a first follow-up in the years 2015 to 2016. Results: 2157 individuals participated in the baseline. Of these, 146 died and 1709 remained in the first follow-up, two years later. Most participants were female, aged up to 60 years, had a stable union and declared themselves to be non-white. Conclusion: the cohort has contributed to the advancement in scientific knowledge of CD. Its results should also support public policies and strategies to improve the health services offered in a way that addresses the real needs of people with CD.